Diagnostic and Prognostic Value of Calprotectin (MRP8/MRP14) in the Blood of Patients with Different Types of Juvenile Idiopathic Arthritis - Ya.Ye. Boiko (Zaslavsky O.Yu., 2016)
Introduction. Determining the levels of S100A8 proteins (alias: MRP8), S100A9 (alias: MRP14) may contribute to early diagnosis of systemic arthritis in children. The objective of the study was to compare blood levels of calprotectin (MRP8/14 (S100A8/9)) in patients with systemic, polyarticular, RF-negative and oligoarticular types of juvenile idiopathic arthritis (JIA) in the active stage of the disease and to investigate the correlation between blood levels of calprotectin (MRP8/14 (S100A8/9)) with clinical and laboratory markers of JIA activity. Results. It was shown that calprotectin blood level was higher in patients with systemic course of the disease (median 13,800 ng/ml) and was significantly different from that of healthy children (median 1,800 ng/ml, p = 0.00002), indicators of patients with articular forms of JIA (median 2,700 ng/ml, p = 0.000008), patients with polyarthritis and negative RF (median 3,800 ng/ml, p = 0.003226) and oligoarthritis (median 2,500 ng/ml, p = 0.000009). The highest calprotectin levels in the blood were found in patients with newly diagnosed systemic JIA: the median was 32,500 ng/ml (from 13,800 to 177,000 ng/ml). A direct correlation of blood calprotectin was established with the rate of JADAS 27 blood activity (p = 0.000009), erythrocyte sedimentation rate (p = 0.000079) and C-reactive protein (p = 0.000058). Conclusions. Calprotectin level in the blood (MRP8/MRP14) (MRP8/14 (S100A8/9)) is one of the indicators that can be used to confirm the diagnosis of systemic JIA and to monitor the activity and effectiveness of therapy.